Effect of fetal hemodynamics on growth in fetuses with single ventricle or transposition of the great arteries. (4th October 2018) - Alsaied, T.; Tseng, S.; King, E.; Hahn, E.; Divanovic, A.; Habli, M.; Cnota, J.
ABSTRACT: Objectives: As birth weight is a critical predictor of outcome in neonates with congenital heart defect (CHD), the common problem of poor fetal growth in this population is clinically important. However, it is not well understood and the impact of fetal hemodynamics on fetal growth and birth weight in those with CHD has not been assessed. In this study, we sought to evaluate the association between combined cardiac output (CCO) and fetal middle cerebral artery (MCA) and umbilical artery (UA) pulsatility indices (PIs) and fetal growth in different subgroups of CHD, and to study the effects of fetal hemodynamics on late gestational weight gain. We hypothesized that fetuses with CHD will have lower CCO and be smaller at birth. Methods: This was a retrospective review of fetal echocardiograms from 67 fetuses diagnosed with hypoplastic left heart syndrome (HLHS, n  = 30), non‐HLHS single ventricle (SV) ( n  = 20) or dextrotransposition of the great arteries (d‐TGA, n  = 17), compared with normal controls ( n  = 42). CCO was calculated using valvar area, velocity–time integral and heart rate and indexed to estimated fetal weight. MCA‐ and UA‐PI were calculated using systolic, diastolic and mean velocities. Fetal biometry was recorded. Regression models were used to study trends in CCO, MCA‐ and UA‐PI and fetal biometry over gestational age. To evaluate fetal weight gain in late gestation, Z ‐scores of estimated fetal weight at 30 weeks and birth weight were compared. Regression analysis was used to determine the associations of CCO, indexed CCO and MCA‐ and UA‐PI at 30 weeks with birth weight, length and head circumference Z ‐scores, in addition to weight gain late in gestation. The gestational age of 30 weeks was chosen based on previous studies that found evidence of poor weight gain in fetuses with CHD in late gestation, starting at around that time. Results: CCO increased with gestation in all four groups but the rate was slower in fetuses with HLHS and in those with SV. MCA‐PI was lower in fetuses with HLHS compared with in those with non‐HLHS‐SV throughout gestation, suggesting different cerebral blood distribution. At the end of gestation, rate of fetal weight gain slowed in those with HLHS and in those with SV (similar to CCO curves), and head circumference growth rate slowed in all groups but controls. CCO, indexed CCO and MCA‐ and UA‐PI did not correlate with any of the birth measurements or with weight gain late in gestation in fetuses with CHD. Conclusions: We found no associations of CCO or MCA‐ and UA‐PI with late gestational weight gain or biometry at birth in fetuses with CHD. This does not support fetal hemodynamics as the primary driver of suboptimal fetal growth in fetuses with SV. Future research could further explain genetic and placental abnormalities that may affect fetal growth in those with CHD. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.